2001
DOI: 10.1677/joe.0.1700071
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metabotropic glutamate receptors in the rat and human testis

Abstract: The G protein-coupled receptor kinase type 4 mediates the homologous desensitisation of type-1 metabotropic glutamate (mGlu1) receptors and is predominantly expressed in the testis. Hence, we searched for the expression of mGlu1 or other mGlu receptor subtypes in rat and human testes. RT-PCR analysis showed the presence of mGlu1, -4 and -5 (but not -2 or -3) receptor mRNA in the rat testis. The presence of mGlu1 and -5 (but not mGlu2/3) receptor proteins was also demonstrated by Western blot analysis. In the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 18 publications
2
69
2
Order By: Relevance
“…ere have recently been several reports indicating that administration of MSG may a ect the sperm count in both neonatal and adult animals (8)(9)(10)(11) and the glutamate receptors and transporters are expressed in the testis and sperm of mice, rats, and humans (12,13). However, the roles of glutamate receptors present in male reproductive organs, including the sperm, have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…ere have recently been several reports indicating that administration of MSG may a ect the sperm count in both neonatal and adult animals (8)(9)(10)(11) and the glutamate receptors and transporters are expressed in the testis and sperm of mice, rats, and humans (12,13). However, the roles of glutamate receptors present in male reproductive organs, including the sperm, have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…7 The need for glutamate homeostasis in the testis derives from the demonstrable roles for this molecule, both as an osmolyte and as an agonist at both N-methyl-D-aspartate and non-N-methyl-D-aspartate-type glutamate receptors. 8,9 Glutamate is the principal free amino acid in the testis, epididymis and semen of most mammalian species; in semen, glutamate is mainly found in the seminal plasma rather than in the spermatozoa. 1 Within the testis itself there is limited evidence for roles for glutamate, though it has been shown that both glutamate and an analog of glutamate (D-aspartate) may modify steroidogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…13 Other glutamate receptor classes including metabotropic types 8,14 are also present on sperm and germinal cells and may thus exert biological effects on the sperm if glutamate levels change.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mGlu1 receptor is expressed in Sertoli cells and mGlu5 receptor in germinal cells with the exception of spermatogonia. 39 In human testes, mGlu5 receptor immunolabeling was intense inside the seminiferous tubuli, whereas mGlu1 receptor immunolabeling was detected in Leydig cells of intertubular spaces, where their activation could likely stimulate testosterone synthesis. 39 In the rat kidney, mGlu2/3 receptors were found in granular cells of the afferent arteriole suggesting a potential role in the control of renin release.…”
Section: Modulation Of Growth Hormone and Prolactin Release By Mglu Rmentioning
confidence: 97%
“…39 In human testes, mGlu5 receptor immunolabeling was intense inside the seminiferous tubuli, whereas mGlu1 receptor immunolabeling was detected in Leydig cells of intertubular spaces, where their activation could likely stimulate testosterone synthesis. 39 In the rat kidney, mGlu2/3 receptors were found in granular cells of the afferent arteriole suggesting a potential role in the control of renin release. 40 mGlu3 receptors were demonstrated to be upregulated in response to persistent hypoxic status such as fibrotic/cirrhotic conditions in the rat liver, exerting protective effects and improving hepatic function, 41 although an agonist of mGlu2/3 receptors had no effect on rat hepatocyte death induced by anoxia.…”
Section: Modulation Of Growth Hormone and Prolactin Release By Mglu Rmentioning
confidence: 97%